2018
DOI: 10.1038/s41598-018-34209-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale enhancement of photoconductivity by localized charge traps in the grain structures of monolayer MoS2

Abstract: We report a method for mapping the nanoscale anomalous enhancement of photoconductivity by localized charge traps in the grain structures of a molybdenum disulfide (MoS2) monolayer. In this work, a monolayer MoS2 film was laterally scanned by a nanoscale conducting probe that was used to make direct contact with the MoS2 surface. Electrical currents and noise maps were measured through the probe. By analyzing the data, we obtained maps for the sheet resistance and charge trap density for the MoS2 grain structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…In previous studies, it was reported that when electrical noises were generated by a small number of trap states with a similar trapping time, a noise PSD spectrum exhibited a scaling behavior of ∼1/ f 2 . 20–22 On the other hand, in the case of numerous trap states with random trapping time, a noise spectrum usually shows ∼1/ f behavior. 20–22 Our results with ∼1/ f behavior indicate that there were numerous trap states with different trapping times in our bulk ITO samples, as reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it was reported that when electrical noises were generated by a small number of trap states with a similar trapping time, a noise PSD spectrum exhibited a scaling behavior of ∼1/ f 2 . 20–22 On the other hand, in the case of numerous trap states with random trapping time, a noise spectrum usually shows ∼1/ f behavior. 20–22 Our results with ∼1/ f behavior indicate that there were numerous trap states with different trapping times in our bulk ITO samples, as reported previously.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Recently, we reported a scanning noise microscopy method that allows one to map the activities of electrical noise sources in lateral and vertical electrical channels at a nanoscale resolution. 20,24,25 In the conducting film, lateral transport is the dominant conduction mechanism between the electrodes. 25 However, such a method has not been utilized for ITO films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main contributions of the voltage drop are R S and R Contact . The resistance of the MoS 2 flake is around 1.6 × 10 3 to 6.4 × 10 5 Ω 58,59 , which is much smaller than the total resistance (>10 8 Ω). On the other hand, the interlayer resistance of the MoS 2 flake is at most 5.1 × 10 4 Ω 60 .…”
Section: Methodsmentioning
confidence: 88%
“…Spin-polarized DFT calculations are carried out using the Vienna ab initio simulation package (VASP) program package 58 within the projector augmented wave (PAW) to explore geometries and electronic properties of MoS 2 . The exchange-correlation functions are described with the generalized gradient approximation (GGA) in the form of the Perdew, Burke, and Ernzernhof (PBE) functional 59 . The DFT-D3 scheme of Grimme for the vdW correction 60 is applied on multiple layers of MoS 2 .…”
Section: Methodsmentioning
confidence: 99%